Diseño y realización hardware de un generador de números aleatorios - Melgarejo Rey, Miguel Alberto; Pirajan Aranguren, Alexis Javier (Ingeniería, 2001)
This article presents the specification , validation and modeling of a HRNG (Hardware Random Number Generator) with 12 bit parallel output format. The working principle of the proposed generator consists on sampling the electrical signal obtained from the thermal noise in a semiconductor, in this sense , two semiconductors devices (BJT and bipolar Zener) have been used and compared. Statistical and spectral analyses have been employed for comparing the noise provided by these devices. Obtained results show an interesting application field for this generator.